Annoyance of time-varying road-traffic noise - KACZMAREK, Tomasz; PREIS, Anna (Archives of Acoustics, 2013)
The aim of the study was to investigate how the time structure of a road-traffic affects the noise annoyance judgment. In a psychoacoustic experiment, the listeners judged noise annoyance of four road-traffic noise scenarios with identical numbers of vehicles and LAeq,T value but different time structure of a road traffic. The traffic structure varied from even to highly clustered across different scenarios. The scenarios were created in the laboratory from a large set of a single vehicle pass-by recordings. The scenarios were additionally filtered with filters corresponding to a typical window transfer function to simulate the situation inside the building. The experimental results showed that there is a significant difference in annoyance judgment for different traffic structures with the same LAeq,T value. The highest annoyance ratings were obtained for even traffic distribution and the most clustered distribution resulted in the lowest annoyance rating. These results correlated well with the averaged loudness, whereas the percentile loudness (N5) and level (L5) predict the opposite results.